ANTIFUNGAL EFFECT OF NIGELLA SATIVA EXTRACT ON FEMALE WISTAR RATS VULVOVAGINAL CANDIDIASIS MODEL - RUSDA, MUHAMMAD (International Journal of Current Pharmaceutical Research, 2020)
Objective: To assess the antifungal effect of Nigella sativa extract on female Wistar rats vulvovaginal candidiasis. Methods: This was an analytic study that assess the therapeutic effect of Nigella sativa in rats’ vulvovaginal candidiasis model. The subjects were 28 rats that had been inoculated with Candida albicans and divided into 4 groups: control group (G1), fluconazole group (G2), Nigella sativa group (G3) and combination of Nigella sativa with fluconazole group (G4). Candida albicans colony was measured to assess the therapeutic effect of the treatment. Results: There were no difference number of Candida albicans colony between all group before inoculation (p = 0,274) and after inoculation (p = 0,323). There were a significant decreased number of Candida albicans colony on the 72 h after the treatment between the three types of treatment with the control group (Nigella sativa group p = 0,002; Fluconazole group p = 0,001; Nigella sativa+fluconazole p = 0,001) Conclusion: Nigella sativa has a potential antifungal effect by reducing the number of Candida albicans colonies.